I would never take preventive medication! Perspectives and information needs of people who underwent predictive tests for rheumatoid arthritis - Mosor, Erika; Stoffer-Marx, Michaela; Steiner, Guenter; Raza, Karim; Stack, Rebecca J.; Simons, Gwenda; Falahee, Marie; Skingle, Diana; Dobrin, Mircia; Schett, Georg; Englbrecht, Matthias; Smolen, Josef S.; et al. (Arthritis & Rheumatism-Arthritis Care & Research, 2019)
OBJECTIVE: Little is known about the experiences, values and needs of people without arthritis who undergo predictive biomarker testing for the development of rheumatoid arthritis (RA). Our study aimed to explore the perspectives of these individuals and describe their information needs. METHODS: A qualitative, multicenter interview study with a thematic analysis was conducted in Austria, Germany and the UK. Individuals who underwent predictive biomarker testing for RA and had a positive test result, but no diagnosis of any inflammatory joint disease, were interviewed. Participants included patients with arthralgia and asymptomatic individuals. Information and education needs were developed from the qualitative codes and themes using the Arthritis Educational Needs Assessment Tool (ENAT) as a frame of reference. RESULTS: Thematic saturation was reached in 34 individuals (76% female; 24 [71%] with arthralgia and 10 [29%] asymptomatic individuals). Thirty-seven codes were summarized into four themes, namely (i) decision making around whether to undergo initial predictive testing, (ii) willingness to consider further predictive tests and/or (iii) preventive interventions, including medication and (iv) varying reactions after receiving a positive test result. Individuals with arthralgia were more likely to be willing to take preventive action, undergo further testing, and experience psychological distress than asymptomatic individuals. All participants expressed the need for tailored, lay-understandable information. CONCLUSION: Individuals at risk of RA are currently the subjects of research aimed at developing better predictive strategies and preventive approaches. Their perceptions and needs should be addressed to inform the future development of interventions combined with education. This article is protected by copyright. All rights reserved.
EVALuna2:102214